Sustainable Technologies for Soil Health and Basmati Rice Productivity in India: Current Research and Future Directions - Shivangi; Omkar Singh; UP Shahi; P K Singh; KK Singh; Pintoo Kumar; Shweta Singh; Vaishali Singh; Adarsh Kumar Meena; Akansha Tyagi (Archives of Current Research International, 2025)
Basmati rice (Oryza sativa L.) is a crucial economic and cultural crop in South Asia, particularly in India and Pakistan. But the intensification of basmati rice farming methods has resulted in notable soil degradation, lower soil organic carbon, imbalances of nutrients, and less biodiversity. The present situation of sustainable technologies meant to improve soil condition and increase basmati rice production is investigated in this thorough research. Research on conservation agriculture, organic amendments, microbial inoculants, precise nutrient management, and climate-smart agricultural methods is compiled in this work. By means of field investigations, meta-analyses, and case studies, we have found interesting approaches concurrently addressing soil health improvement and yield optimisation. This review emphasizes important information gaps including limited long-term studies in many agroecological areas, insufficient economic analysis, and poor evaluation of technological adoption hurdles. Emphasizing the requirement of integrated approaches combining several sustainable technologies, increased stakeholder involvement, and policy frameworks encouraging sustainable soil management practices should be the goal of future studies. This thorough study offers evidence-based recommendations for creating all-encompassing plans for sustainable basmati rice output systems to researchers, legislators, and industry experts.